Conditions of qualitative movement of dynamic controlled systems - Антонов, В. К. (Proceedings of National Aviation University (archive), 2021)
Conditions of optimality of motion of controlled dynamical systems, obtained by introducing to Functional quality of the additional function of the minimal value of the functional in the statement variational problems according to Hamilton and in accordance with the principle of optimality of Belman